Clinical and Epidemiological Aspects Related to Infection of Orthopedic Prostheses in Argentinean Children. A 10-Year Period Study. (4th October 2017) - Vergara Lobo, Carlos Mauricio; Ferolla, Fausto M; Contreras, Elen; Carballo, Carolina; Yfran, Walter; Pannunzio, Eugenia; Anteliz, Eliana; Reviriego, Juan; Escalada, Maria; Rositto, Gabriel; Legarreta, Carlos; Cazes, Claudia I; et al.
Abstract: Background: Management of orthopedic prostheses infections (PI) in children is a main challenge, not only for the complexity of the disease but also for the scarce of evidence in this field. Objectives: To describe the burden of PI and to analyze clinical and epidemiological aspects in pediatric patients. Methods: Retrospective study in a tertiary pediatric hospital. Clinical charts of patients <18 years who underwent surgery for bone and/or joint implantation at "R. Gutierrez" Children's Hospital in Buenos Aires from January 2007 to December 2016 were reviewed, and all PI cases were analyzed. PI was defined as early (E) when presentation was within 3 months of prothesis implantation, delayed (D) when presenting between 3–24 months and late (L) if presenting beyond 2 years. Results: 811 surgeries performed; 89 PI detected: E( n = 63); D( n = 9), L( n = 17); 58% male; median(m) age: 13 years (range[ r ] 4–20); m hospital stay 30 days ( r 6–180). Annual incidence: 11% (CI95%: 8.9–13.1) (Figure 1). Underlying conditions: scoliosis (58.4%), malignancy (16.8%). Clinical features are detailed in Figure 2. Bacterial isolation in 63 (70.8%) cases, 51(57.3%) with a single microorganism (Figure 3). Gram(+) bacteria were isolated in 58% of E PI, 86% of D PI and 49% of L PI. Gram(−) pathogens in 49% of E PI and in 38% of L PI. Three febrile PI (3, 4%) had Gram(+) bacteremia, two of them L PI. No differences were seen in white blood cell count (WBC) and C-reactive protein(CRP) levels on admission in children with and without bacteremia, nor among the different types of PI; m WBC 9000/mm 3 ( r 3200–25550), m CRP 37 mg/l (r 1–270). WBC on admission in MRSA PI was significantly higher, P < 0, 01. Duration of EV treatment was different according to type of microorganism ( P 0.03), higher in PI by Gram(−). Forty-eight (53.9%) cases continued with trimethoprim-sulfamoxazole orally, without side effects requiring its discontinuation. Total treatment duration (m): 189 days ( r 28–756). Eighty-two children (92.1%) underwent surgical toilette, 37 (45.1%) required more than one. Six (6.7%) presented relapse and eight (9%) reinfection. Conclusion: · PI in children is a considerable burden, with high morbidity. · Incidence of bacteremia was low. · Results of the study could help to delineate preventive strategies and improve decision making in PI in children. Disclosures: All authors No reported disclosures.